PEMENUHAN HAK-HAK KHUSUS NARAPIDANA PEREMPUAN (STUDI PADA LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS III TERNATE) - Anshar Anshar; Syawal Abdulajid (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
This paper examines the implementation of the fulfillment of the special rights of women prisoners under certain conditions, such as menstruation, pregnancy, childbirth or breastfeeding who take the object of study at the Class III Ternate Women's Prison. The research was conducted using empirical legal research type by collecting primary and secondary data with data collection techniques both in field studies and literature studies. The results showed that the fulfillment of special rights for women prisoners had not been implemented properly. This is influenced by several factors, one of which is the absence of legal instruments that can standardize the fulfillment of special rights for women prisoners. So that in the future there is a need for seriousness from the state to compile and enforce these legal instruments so that they can be immediately applied to every women's penitentiary throughout Indonesia.